2019
DOI: 10.1111/ppl.12892
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation and endogenous abscisic acid in the moss Physcomitrella patens during acquisition of desiccation tolerance

Abstract: The moss Physcomitrella patens has been used as a model organism to study the induction of desiccation tolerance (DT), but links between dehydration rate, the accumulation of endogenous abscisic acid (ABA) and DT remain unclear. In this study, we show that prolonged acclimation of P. patens at 89% relative humidity (RH) [−16 MPa] can induce tolerance of desiccation at 33% RH (−153 MPa) in both protonema and gametophore stages. During acclimation, significant endogenous ABA accumulation occurred after 1 day in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Although P. patens is not considered to be a DT moss with a constitutive mechanism of protection from desiccation (Pressel and Duckett 2010 ; Koster et al 2010 ), it has been shown that this moss has an inducible molecular mechanism that is activated in response to cold (Beike et al 2015 ), dehydration (Koster et al 2010 ), and ABA and salt treatments (Khraiwesh et al 2015 ). Recently, it has been reported that 6 and 9 d of acclimation to 69 % RH are required to induce DT at 33 % RH in protonemal and gametophore tissues of P. patens , respectively (Rathnayake et al 2019 ). The results obtained using the Austin protocol indicate that P. replicatum is an FDT moss that is able to recover photosynthesis after rapid and slow dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although P. patens is not considered to be a DT moss with a constitutive mechanism of protection from desiccation (Pressel and Duckett 2010 ; Koster et al 2010 ), it has been shown that this moss has an inducible molecular mechanism that is activated in response to cold (Beike et al 2015 ), dehydration (Koster et al 2010 ), and ABA and salt treatments (Khraiwesh et al 2015 ). Recently, it has been reported that 6 and 9 d of acclimation to 69 % RH are required to induce DT at 33 % RH in protonemal and gametophore tissues of P. patens , respectively (Rathnayake et al 2019 ). The results obtained using the Austin protocol indicate that P. replicatum is an FDT moss that is able to recover photosynthesis after rapid and slow dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Drought causes water deficit (Bray 1997) and may even lead to desiccation, a condition in which bound water is the only water that remains in plant cells (Ramanjulu and Bartels, 2002). Although seeds of higher plants can withstand desiccation (Bewley 1979), the vegetative tissues of most plants do not tolerate a water content below 30-60 % (Challabathula and Bartels 2013;Zhang and Bartels 2018).…”
Section: Introductionmentioning
confidence: 99%
“…AWC was measured in gametophytes of S. caninervis at various time points during the D-R process. AWC curves, plotting the water content on a dry weight basis, were produced using the following formula (Rathnayake et al, 2019): AWC (g g -1 DW) = (FW-DW)/ DW; FW indicates the fresh weight measured at every time point during the D-R process, and DW indicates the weight measured after drying for 48 h at 80°C in an oven.…”
Section: Physiological Indicator Measurementsmentioning
confidence: 99%